Speech Act Strategies in Anies Matta’s Address at the Summit on the Palestinian Genocide - Ahmad Jadir Labib; Silvira Hardiyanti (CV. ULIL ALBAB CORP, 2026)
This article examines the speech act strategies employed in Anies Matta’s address at the 2024 Riyadh Summit within the context of international diplomacy responding to the genocide in Palestine. Using a descriptive qualitative approach and John Searle’s speech act theory, this study analyzes five categories of speech acts: representatives, directives, commissives, expressives, and declaratives. The analysis is based on the speech transcript and conducted through a pragmatic discourse analysis framework. The findings reveal that the speech is not only imbued with moral and ideological dimensions but also functions as a strategic communicative instrument to assert Indonesia’s position as a consistent and principled diplomatic actor in its support for Palestine. The geopolitical context, particularly the normalization of Arab–Israeli relations, further amplifies the urgency of the speech as a form of symbolic resistance to the depoliticization of the Palestinian issue. The linguistic strategies employed by Anies Matta demonstrate an integration of diplomatic communication, national identity, and humanitarian advocacy, highlighting the potential of language as an instrument of foreign policy. This study contributes to the development of political pragmatics, ethical diplomacy, and linguistically oriented international relations research.